Vulnerable newborn types: Analysis of subnational, population‐based birth cohorts for 541 285 live births in 23 countries, 2000–2021 - Erchick, D. J.; Hazel, E. A.; Katz, J.; Lee, A. C. C.; Diaz, M.; Wu, L. S. F.; Yoshida, S.; Bahl, R.; Grandi, C.; Labrique, A. B.; Rashid, M.; Ahmed, S.; et al. (Wiley, 2025)
Objective To examine prevalence of novel newborn types among 541 285 live births in 23 countries from 2000 to 2021.